Nature's Return : An Environmental History of Congaree National Park - Kinzer, Mark (Book collections on Project MUSE., 2017)
"Located at the confluence of the Congaree and Wateree Rivers in central South Carolina, Congaree National Park protects the nation's largest intact expanse of old-growth bottomland hardwood forest. Modern visitors to the park enjoy a pristine landscape that seems ancient and untouched by human hands, but in truth its history is far different. In Nature's Return, Mark Kinzer examines the successive waves of inhabitants, visitors, and landowners of this region by synthesizing information from property and census records, studies of forest succession, tree-ring analyses, slave narratives, and historical news accounts. Established in 1976, Congaree National Park contains within its boundaries nearly twenty-seven thousand acres of protected uplands, floodplains, and swamps. Once exploited by humans for farming, cattle grazing, plantation agriculture, and logging, the park area is now used gently for recreation and conservation. Although the impact of farming, grazing, and logging in the park was far less extensive than in other river swamps across the Southeast, it is still evident to those who know where to look. Today Congaree National Park is a forest of vast flats and winding sloughs where champion trees dot the landscape. Indeed its history of human use and conservation make it a valuable laboratory for the study not only of flora and fauna but also of anthropology and modern history. As the impact of human disturbance fades, the Congaree's stature as one of the most important natural areas in the eastern United States only continues to grow"--Provided by publisher.